The Syrian Crisis and Its Impact on Iraq after 2011 - Abbas Ghadhban , Lect .Dr. Abather (Basra studies journal, 2025)
The Syrian crisis is one of the most complex crises in the Middle East, with its effects extending beyond Syria’s borders to significantly impact neighboring countries, particularly Iraq. This is due to the geographical, demographic, and political interconnectedness between the two countries. The Syrian crisis has posed major challenges for Iraq across various domains, including security, politics, economy, and society. In accordance with the ongoing complexities of the Syrian scene, Iraq finds itself in a sensitive position that requires balancing its local interests with regional political developments. Despite the deep-rooted and intertwined relations between the two neighboring countries at all levels, Iraq is dealing seriously and cautiously with the recent shifts and developments in Syria, especially after the successive crises Syria has faced since 2011. Therefore, cautious diplomacy can be described as the official stance of Iraq, with a strategy based on prudence and patience until the situation becomes clearer in this complex and entangled scene. This approach takes into account avoiding hasty decisions that could negatively impact Iraqi national security and its internal and regional stability. The Syrian crisis has had complex political, security, economic, and social repercussions, leaving negative effects on Iraq and creating significant challenges.